1999
DOI: 10.1080/08035259950170105
|View full text |Cite
|
Sign up to set email alerts
|

Highchair accidents

Abstract: In order to establish guidelines for highchair accident prevention we investigated causes, mode and complications of highchair accidents by the following methods: The charts of 103 children attending our Accident & Emergency department for highchair related injuries were studied retrospectively. Questionnaires were sent to the parents to obtain detailed information about the mode of accident. They were also asked to suggest preventive measures. In addition, a random sample survey was performed with 163 familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 2 publications
2
7
0
1
Order By: Relevance
“…Also, more than half agreed that many child safety products have unclear or complicated instructions. These findings are in agreement with the study by Mayr, in which 80% of parents interviewed would appreciate a preinstallation of car restraints, 54% requested more informative instructions for users and 33% asked for products with better stability (Mayr et al 1999). This information is useful to determine the link between parental perception of safety equipment and use (Ehrlich et al 2001), as well as parental misconceptions of safety equipment, which may jeopardize the safety of their children (Ramsey et al 2000).…”
Section: Discussionsupporting
confidence: 82%
“…Also, more than half agreed that many child safety products have unclear or complicated instructions. These findings are in agreement with the study by Mayr, in which 80% of parents interviewed would appreciate a preinstallation of car restraints, 54% requested more informative instructions for users and 33% asked for products with better stability (Mayr et al 1999). This information is useful to determine the link between parental perception of safety equipment and use (Ehrlich et al 2001), as well as parental misconceptions of safety equipment, which may jeopardize the safety of their children (Ramsey et al 2000).…”
Section: Discussionsupporting
confidence: 82%
“…17 Other research indicates that restraint use among children sustaining injuries associated with high chairs may be as low as 3.2%. 18 Therefore, it is likely that parents and other child caretakers could greatly reduce the number of high chair-related injuries by consistently engaging the safety restraints. Caregivers should be reminded that the tray portion of the high chair is not a safety restraint, despite popular belief to the contrary.…”
Section: Discussionmentioning
confidence: 99%
“…When averaging across all fall trials for a fall height, impact surface, and impact location, none of these average peak angular accelerations exceeded the 10,000 rad/s 2 concussion threshold lower bound. Mayr et al (1999) reported 13.6% of children (7–30 months old; mean=13 months) experienced a concussion following a fall from a highchair. Tarantino et al (1999) reported 11% of 167 children (< 10 months old) experienced a closed head injury following a < 4 ft fall.…”
Section: Discussionmentioning
confidence: 99%
“…Both children were under 2 years old. Mayr et al (1999) reports 16% of 103 children 7–30 months experienced a skull fracture following a fall from a highchair. Tarantino et al (1999) reported 17% of 167 infants < 10 months old had a skull fracture in falls < 4 ft. Future work will incorporate the fall kinematic data in this study with published pediatric skull ultimate stress data (Coats and Margulies 2006) to develop risk curves for skull fracture.…”
Section: Discussionmentioning
confidence: 99%